2021
DOI: 10.1097/as9.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Bottoms Up: A History of Rectal Nutrition From 1870 to 1920

Abstract: From the 1870s through the early 20th century, physicians frequently relied upon nutritive enemata to succor patients suffering from bowel obstructions and other disorders of the gastrointestinal system. Far from extraordinary or outlandish, this therapy was used on paupers and presidents alike, including on Garfield and McKinley after their assassination attempts. The medical milieu of the late 19th century provided particularly promising circumstances for its practice, with the rise of allopathic medicine ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…7 In the early 20th century, scientific advances in nutrition physiology concluded that nutrients (specifically fats and proteins) are not absorbed to any significant extent through the rectal mucosa, and the practice largely vanished by 1915. 7 Although fluids (water, saline) can be absorbed through the rectal mucosa, intravenous administration of fluids replaced hydration via the rectal route by the mid-20th century. Rectal administration of fluids can be attempted for fluid resuscitation in emergency situations in remote settings when it is the only treatment available.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7 In the early 20th century, scientific advances in nutrition physiology concluded that nutrients (specifically fats and proteins) are not absorbed to any significant extent through the rectal mucosa, and the practice largely vanished by 1915. 7 Although fluids (water, saline) can be absorbed through the rectal mucosa, intravenous administration of fluids replaced hydration via the rectal route by the mid-20th century. Rectal administration of fluids can be attempted for fluid resuscitation in emergency situations in remote settings when it is the only treatment available.…”
mentioning
confidence: 99%
“…“Nutritive enemata” is of historic interest only, having been used in US medicine for patients with bowel disorders dating back to the 1870s and up through the early 20th century. This method of feeding was attempted on Presidents Garfield and McKinley prior to their deaths from gunshot injuries inflicted by assassins . In the early 20th century, scientific advances in nutrition physiology concluded that nutrients (specifically fats and proteins) are not absorbed to any significant extent through the rectal mucosa, and the practice largely vanished by 1915 …”
mentioning
confidence: 99%
See 1 more Smart Citation